MICP mediated by indigenous bacteria isolated from tailings for biocementation for reduction of wind erosion - Maureira, Alejandro; Zapata, Manuel; Olave, Jorge; Jeison, David; Wong, Liey-Si; Panico, Antonio; Hernández, Pía; Cisternas, Luis A.; Rivas, Mariella (Frontiers in Bioengineering and Biotechnology, 2024)
In this study, native ureolytic bacteria were isolated from copper tailings soils to perform microbial-induced carbonate precipitation (MICP) tests and evaluate their potential for biocement formation and their contribution to reduce the dispersion of particulate matter into the environment from tailings containing potentially toxic elements. It was possible to isolate a total of 46 bacteria; among them only three showed ureolytic activity: Priestia megaterium T130-1, Paenibacillus sp. T130-13 and Staphylococcus sp. T130-14. Biocement cores were made by mixing tailings with the isolated bacteria in presence of urea, resulting similar to those obtained with Sporosarcina pasteurii and Bacillus subtilis used as positive control. Indeed, XRD analysis conducted on biocement showed the presence of microcline (B. subtilis 17%; P. megaterium 11. 9%), clinochlore (S. pasteurii, 6.9%) and magnesiumhornblende (Paenibacillus sp. 17.8%; P. megaterium 14.6%); all these compounds were not initially present in the tailings soils. Moreover the presence of calcite (control 0.828%; Paenibacillus sp. 5.4%) and hematite (control 0.989%; B. subtilis 6.4%) was also significant unlike the untreated control. The development of biofilms containing abundant amount of Ca, C, and O on microscopic soil particles was evidenced by means of FE-SEM-EDX and XRD. Wind tunnel tests were carried out to investigate the resistance of biocement samples, accounted for a mass loss five holds lower than the control, i.e., the rate of wind erosion in the control corresponded to 82 g/m2h while for the biocement treated with Paenibacillus sp. it corresponded to only 16.371 g/m2h. Finally, in compression tests, the biocement samples prepared with P. megaterium (28.578 psi) and Paenibacillus sp. (28.404 psi) showed values similar to those obtained with S. pasteurii (27.102 psi), but significantly higher if compared to the control (15.427 psi), thus improving the compression resistance capacity of the samples by 85.2% and 84.1% with respect to the control. According to the results obtained, the biocement samples generated with the native strains showed improvements in the mechanical properties of the soil supporting them as potential candidates in applications for the stabilization of mining liabilities in open environments using bioaugmentation strategies with native strains isolated from the same mine tailing.